Bad day when they saw you leave the kingdom of the beasts: Projections of evil on the tragic figure in Chantal Maillard’s Medea - Martín Isabel, Hugo (Amaltea. Revista de Mitocrítica, 2024)
In her book of poems (2020), the poet and philosopher Chantal Maillard rewrites the "prosopomyth" of Medea. In this long dramatic monologue, Maillard projects her ethical concept of "compassion", coined in her essay La compasión difícil (2019), onto the magician of Yolco. We will analyse the themes of Medea’s "prosopomyth" that appear throughout the poem and observe to what extent and in what way they are used to explain and exemplify the concept of "compassion". To do so, we use the philosophical terminology of evil and compassion established by María Zambrano, Ana Carrasco-Conde and Maillard herself.